Chaetocin inhibits IBMX-induced melanogenesis in B16F10 mouse melanoma cells through activation of ERK. (5th February 2016) - Bae, Jung-Soo; Han, Mira; Yao, Cheng; Chung, Jin Ho
Abstract: Chaetocin is a natural product isolated from Chaetomium species that has anti-bacterial and anti-myeloma activities. In this study, we investigated the inhibitory effect of chaetocin on melanogenesis and the underlying mechanisms in B16F10 mouse melanoma cells. In the present study, chaetocin significantly inhibited IBMX-induced melanin production and tyrosinase activity without any cytotoxicity. Furthermore, chaetocin down-regulated both the protein and mRNA levels of tyrosinase, which is a specific enzyme that catalyzes the conversion of tyrosine to melanin. We also observed that the protein level of MITF was significantly reduced by chaetocin treatment. In addition, we found that the anti-melanogenic effect of chaetocin was suppressed by treatment with the specific ERK inhibitor (PD98059). Accordingly, chaetocin inhibited melanogenesis via suppressing the protein level of MITF followed by activation of the ERK signaling pathway. These data suggest that chaetocin may be a potential anti-melanogenic agent for use in skin-whitening cosmetics and a topical agent for treatment of hyperpigmentation disorders. Highlights: Chaetocin has little cytotoxic effect in B16F10 mouse melanoma cells. Chaetocin found to attenuate 3-isobutyl-1-methylxanthine (IBMX)-induced melanin synthesis. Chaetocin inhibited IBMX-induced melanogenesis via activation of the ERK pathway.